Pro .NET 2.0 Code and Design Standards in C# - Horner, Mark.; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
This book is special, because for the first time you get an easy-to-follow set of code and design standards that addresses the basic needs of .NET developers and application architects. The material is presented in a what, why, where, and how format, so it's easy to understand a given topic and apply the solution. The format facilitates fast understanding and quick reference$1 (Bjust what you need when you're under pressure. The authors have done the research for you, and they identify and discuss common options. Where there is a choice, there is analysis to guide you. Techniques are reusable across all versions of .NET and beyond. Pro .NET 2.0 Code and Design Standards in C# is intuitive and based on industry best practices. While it showcases the C# language, its universal style makes it suitable for all .NET development projects, whatever the language.s
Code Policy Standards -- Code Policy -- Code Structure -- Code Development -- Code Documentation -- Design Policy Standards -- Design Policy -- Design Structure -- Design Development -- Design Documentation -- Pattern Standards -- Patterns -- Creational Patterns -- Structural Patterns -- Behavioral Patterns.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books